The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1678-91992009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Snake antivenoms: adverse reactions and production technology

Abstract: Antivenoms have been widely used for more than a century for treating snakebites and other accidents with poisonous animals. Despite their efficacy, the use of heterologous antivenoms involves the possibility of adverse reactions due to activation of the immune system. In this paper, alternatives for antivenom production already in use were evaluated in light of their ability to minimize the occurrence of adverse reactions. These effects were classified according to their molecular mechanism as: anaphylactic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 80 publications
1
51
0
Order By: Relevance
“…Segura et al (6) observed that the reduction of phenol to a concentration of 0.15 g% maintains the physical stability of antivenoms and decreases their liability of forming aggregates (6). Other researchers corroborate such finding, especially if the protein content is elevated, which may lead to loss of antivenom activity and to adverse reactions due to activation of the immune response (4,21,(26)(27)(28)(29)(30). At the same time, the decrease of m-cresol concentrations may diminish antivenom toxicity to humans, particularly in certain circumstances in which high doses are required, such as in the two cases mentioned by Buntain (31) and Ganthavorn (32) (750 to 1150 mL of antivenom).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Segura et al (6) observed that the reduction of phenol to a concentration of 0.15 g% maintains the physical stability of antivenoms and decreases their liability of forming aggregates (6). Other researchers corroborate such finding, especially if the protein content is elevated, which may lead to loss of antivenom activity and to adverse reactions due to activation of the immune response (4,21,(26)(27)(28)(29)(30). At the same time, the decrease of m-cresol concentrations may diminish antivenom toxicity to humans, particularly in certain circumstances in which high doses are required, such as in the two cases mentioned by Buntain (31) and Ganthavorn (32) (750 to 1150 mL of antivenom).…”
mentioning
confidence: 78%
“…Turbidity in equine antivenoms depends, at least, in one way, on the interaction between initial protein concentration in the serum, and addition of phenol during fractionation of serum (10). Protein aggregation -besides loss of activity and safety of antivenom -is another important indicator of product instability caused by phenols, which are hydrophobic substances that may induce an increase in protein denaturation (3,12,21). García et al (12) found differences in the augmentation of aggregate levels and dimmers among antivenoms stored for three years that were devoid of phenol and contained different preservatives, meaning that these substances could accelerate the normal denaturation process.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, antiserum composed of specific immunoglobulins is the only treatment for snake envenomation, but there are ongoing issues with availability, effectiveness and dosing [19,20]. These antivenoms neutralize the toxicity and lethality of specific venoms, but their administration is often related with significant clinical side effects [21,22]. Additionally, the production of antivenoms is associated with high costs related to animal maintenance and also comes across animal welfare concerns, which instigates the search for innovative products for snakebite therapy [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned drawbacks point to a central problem faced by antivenoms: access. Low production, inadequate distribution chains, and the need for species and regionspecific products thwart global antivenom availability (14)(15)(16). The result of low output and high production costs are antivenoms that are unaffordable to those who need them most.…”
Section: Introductionmentioning
confidence: 99%